Predicting Surgical Mortality After Congenital Heart Surgeries Using Risk Adjustment in Congenital Heart Surgery-1 (RACHS-1) Risk Scoring System: A Retrospective Analysis in A Single Tertiary Center - Bajracharya, Smriti Mahaju; Joshi, Dikshya; Pradhan, Sidhartha (Nepalese Heart Journal, 2023)
Objective: The main objective of our study was to analyze the in-hospital mortality in children who underwent surgery for congenital heart defects in a single tertiary cardiac center in Nepal using RACHS-1 risk score during 6 year period.Methods: After approval from Institutional Review Board, retrospective data analysis were performed from June 2013 to June 2019 at Shahid Gangalal National Heart Centre. Patients younger than 14 years, who underwent cardiac surgery for congenital heart defects, were enrolled. Data from patient records regarding the age, gender, weight, diagnosis, procedures performed, cardio‑pulmonary bypass (CPB) time and aortic cross‑clamp (AoX) were obtained. The operations were classifed according to the six RACHS-1 categories and patients were allotted to RACHS-1 categories retrospectively by matching the procedure of each patient with a risk category.Results: Two thousand four hundred and seventeen patients underwent surgeries for congenital heart diseases who were classifed according to the RACHS‑1 score. Among the patients, 56.1 % were male and 20.1 % were younger than one year of age. The mortality was 1.5%,13.3%, 21.7% and 73.4% for category 1, 2, 3 and 4 respectively. The overall ability of the RACHS‑1 classifcation to predict in‑hospital mortality Area under the ROC curve was 0.736 with 95% confdence interval (CI) of 0.709-0.763.Conclusion: The RACHS‑1 classification is applicable to our pediatric populations which was a useful and easily applicable tool, requiring only very few data for mortality risk in our hospital although there are other factors that have an impact on the mortality.